Tropical rainforest degradation in Indonesia: Threat and hope in the landscape of mountain forest to mangrove swamp - Djohan, Tjut Sugandawaty / T. S. (Faculty of Biology Universitas Gadjah Mada, 2013)
Indonesia is one of the countries has extensive forest cover, but has the highest rates of deforestation. The deforestation occurred from watershed to the swamp areas in the landscape. Large areas of the tropical peat swamp-forest in Riau were changed to Acasia spp. and to oil palm, Elaeis guineensis, plantations. Similarly, the forest cover changed into the plantations were also occurred in Kalimantan and many places in Indonesia. In 1996-1997, large area of mangrove forest in Segara Anakan Cilacap was also converted into the intensive shrimp-ponds, which were failed and abandoned, then these abandoned shrimp-ponds were colonized by mangrove shrubs. The lost of the forest due the forest use changes and logging in the mountain forest also leaved a big gap in the forest. These forest gaps were also invaded by the invasive species, Eupatorium odoratum, and Lantana camara. Their present out-competed the seedlings of both the natural and planted trees. The deforestation also threatened the native animal biodiversities. To over come the deforestation, so far many conservation efforts were implemented through many conservation projects, but were not succeed. However, recently there is a hope, a program reforestation in the degraded land through the corporate social responsibility (CSR) program is established. However, the success of replanting the native trees is also depended on to the involvement of the local community. Thus the local should be part of the programs. The incentive for the local should be based on the survival of the planted tree seedlings, which grow up to reproduce their new generations.